2021
DOI: 10.1016/j.ejmp.2021.05.003
|View full text |Cite
|
Sign up to set email alerts
|

A review of deep learning based methods for medical image multi-organ segmentation

Abstract: Deep learning has revolutionized image processing and achieved the-state-of-art performance in many medical image segmentation tasks. Many deep learning-based methods have been published to segment different parts of the body for different medical applications. It is necessary to summarize the current state of development for deep learning in the field of medical image segmentation. In this paper, we aim to provide a comprehensive review with a focus on multi-organ image segmentation, which is crucial for radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(92 citation statements)
references
References 227 publications
(155 reference statements)
1
72
0
Order By: Relevance
“…Deep learning-based (DL) automatic contouring for radiotherapy has evolved over the past years leading to clinical implementation at many institutes and for many treatment sites. Significant time saving compared to both manual contouring and atlas-based contouring methods is achieved [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] . Even though the majority of current clinical tools still use atlas-based auto-contouring, DL-contouring is being offered more often recently [5] , [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning-based (DL) automatic contouring for radiotherapy has evolved over the past years leading to clinical implementation at many institutes and for many treatment sites. Significant time saving compared to both manual contouring and atlas-based contouring methods is achieved [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] . Even though the majority of current clinical tools still use atlas-based auto-contouring, DL-contouring is being offered more often recently [5] , [9] .…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that while deep learning methods have shown good promise in object classification challenges because of their learning ability using feature sets, recent literature reports have suggested that their accuracies in the domain of medical image segmentation need further improvement [75]. Deep learning segmentation methods have been reported to also lack pixel-level accuracy without the application of further processing [76,77]. This is primarily because most of them work on the feature level rather than the pixel level for image segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…This is primarily because most of them work on the feature level rather than the pixel level for image segmentation. In addition, the use of deep learning methods for image segmentation is currently being impaired because of factors such as the need for more datasets for continuous training, lack of memory-efficient models for both training and inference evaluation [76], limited reference information for accurate validation [78], and the possibility of over-fitted results [79]. Considering the 5400 datasets used for evaluation experimentation, we believe our method shows generalization in relation to skin lesion segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…In medical image segmentation scenarios, semantic segmentation classifies each pixel of a medical image and provides both location and rich morphology features, such as shape type (round, oval, lobular and irregular) and margin type (spiculate, ill-defined, obscured and circumscribed) [ 12 ]. DL based algorithms are the data-driven machine learning paradigm, which has an intrinsic ability to learn deep and discriminative features from data without human intervention, and thence, outperform the traditional image segmentation methods [ 13 ]. Previously, DL based solutions segmented abnormities by sliding the image block with fixed-size which is intercepted by a square window centered on the target pixel.…”
Section: Introductionmentioning
confidence: 99%